Endotoxin Contamination of Large Volume Parenterals as Detected by Limulus Amebocyte Lysate as an Alternative to Rabbit Pyrogen Test (Journal of Sciences, Islamic Republic of Iran)
The possibility of replacing the rabbit pyrogen test by the Limulus Amebocyte lysate (LAL) test, as a final release test for Large Volume Parenterals (LVPs) was investigated. The sensitivity and specificity of the LAL test and rabbit pyrogen assay were studied by means of artificially contaminated parenterals. Various LVPs (mostly containing electrolytes) were spiked with 0.5 and 5 EUlml of E.coli 01 11 :B4 endotoxin (Lambda =0.5 EUIml). The pH of the formulations were measured, and if necessary, adjusted to 5.5 - 8.0 by NaOH or HC1. Four of the products showed significant responses to the LAL test when the endotoxin concentration was 0.1 nglml. However, the remaining formulations required some degree of dilution prior to the test to overcome inhibition. The inhibitory effect caused by cations on the LAL reaction is enhanced by increases in valency. Therefore, the difference between the products in responding to the LAL test have resulted from shifts in the electrokinetic potentials between the LAL and the endotoxin. The rabbit test response was insignificant for all the solutions. The LAL test was found to be useful for the detection of bacterial endotoxin in LVPs. It also has the advantage of being more sensitive, rapid and reproducible than the rabbit pyrogen test